2015
DOI: 10.1108/jocm-01-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and performance of SMEs in the services industry

Abstract: Purpose – The purpose of this paper is to examine both the sources of competitiveness of small and medium- sized enterprises (SMEs) in the services industry measured by their capability to grow, and the relative importance of each of these sources. More specifically, the resources and capabilities of Spanish SMEs in the services industry that may become sources of competitive advantage are analysed. Design/methodology/approach – In order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 77 publications
1
54
0
1
Order By: Relevance
“…Thus, the concept of environment and nature are frequently referred to when macro-environmental forces are considered in the current business environment. Rodríguez-Gutiérrez et al [6] point out that research into SMEs has increased in the previous decade due to the significant contribution of this business sector to the ultimate performance of the economy. The traditional assertion that large firms are the major contributors to the economy is being challenged as the role of SMEs in the contemporary business environments is becoming better understood [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the concept of environment and nature are frequently referred to when macro-environmental forces are considered in the current business environment. Rodríguez-Gutiérrez et al [6] point out that research into SMEs has increased in the previous decade due to the significant contribution of this business sector to the ultimate performance of the economy. The traditional assertion that large firms are the major contributors to the economy is being challenged as the role of SMEs in the contemporary business environments is becoming better understood [7].…”
Section: Introductionmentioning
confidence: 99%
“…Rodríguez, Moreno, Tejada (2015) Empirical research conducted on data collected through survey from 1,122 Spanish SMEs during 2011 and early 2012. This paper analyses the source of competitiveness of SMEs in the service industry.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ha-Brookshire [26] firm performance is a complex concept to define and the complexity of the definition is even more entrenched within the context of SMEs operations. Consistently, Rodríguez-Gutiérrez et al [24] argue that a vast difference found in firms is the main reason why the definition of business performance is challenging. Thus, there is a need to consider how firm performance can be assessed within the context of SMEs which have substantive differences contrasted with large businesses [8].…”
Section: Firm Performancementioning
confidence: 93%
“…Firm performance constitutes the second construct in this study. Firm performance is not a new concept in the field of business research [24]. However, despite its prominence in latent literature, the construct of firm performance is challenged by incongruences pertaining to indicators being selected based on the researcher's convenience [25].…”
Section: Firm Performancementioning
confidence: 99%
See 1 more Smart Citation